Study of Adoption Level of Improved Buffalo Husbandry Practices in Peri-Urban Areas of Surat City of Gujarat, India (Indian Journal of Animal Production and Management, 2024)
The present study was conducted in the peri urban areas of Surat city of Gujarat. Total fifty  buffalo farm owners were randomly selected and  interviewed for the questionnaire prepared about  improved buffalo husbandry practices adopted by  them. The findings indicated that majority of buffalo  farm owners had medium adoption level on different  component of improved buffalo husbandry  practices viz. 72% for housing, 74% for feeding,  64% for breeding, 68% for healthcare, 74% for  milking management and 74% for calf rearing. The  overall adoption levels of the respondents in  improved buffalo husbandry practices fall under  low, medium and high categories are 18%, 66% and  16%, respectively. The adoption index of different  aspect of improved buffalo husbandry practices of  housing, feeding, breeding, health care, milking and  calf rearing were 49.4, 34.3, 67, 52.5, 55.9 and  63.7%, respectively and overall adoption index of  improved buffalo husbandry practices was 53.8%  which indicated moderate adoption level of buffalo  farm owners in the study area.
Keywords: buffalo husbandry practices; adoption; peri-urban areas